Questions of Morphology (non-derivative interjections, negation as a grammatical and morphological category) - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2024)
The issues considered in this article (non-derivative elements as a type of interjections and grammatical-morphological category of negation) are insufficiently discussed or staying as a subject of  disagreement in the theoretical morphology of the modern Armenian language.The analysis leads to the following beliefs. Firstly, onomatopoeia, despite semantic, morphemic-phonetic, as well as partially word-formation-functional differences in comparison with other types of interjections (affective and vocative), nevertheless have significant similarities with the above two types of interjections by common partial features, therefore, at least conditionally can be placed in the system of parts of speech, called an interjection, as a separate, third type of this. Secondly, the grammatical category of negation at the morphological level of the Armenian language has its inherent semantic (grammatical meaning) and formal (grammatical means of expression) group features and, therefore, can be conceived and perceived as one of the grammatical categories inherent in the verb.
Keywords: non-derivative interjection; part of speech; type; volitional; sensual; onomatopoeia; negation; morphological category; grammatical meaning; grammatical index; negative particles